Penyelesaian Sengketa Perjanjian Jual Beli Beras Program BPNT Mitra Bulog Dengan E-Warong di Kabupaten Banjarnegara - Faozi, Deva Nur (Proceedings Series on Social Sciences & Humanities, 2024)
The economic growth of a country with low per capita income but prosperous in the future with a high population growth rate, then the country is categorized as a poor country. Poverty remains a big problem for Indonesia to this day, even the government has not been able to overcome or resolve the problem of poverty. Indonesia has issued a program to accelerate poverty reduction, requiring integrated coordination between parties in formulating and implementing policies. This coordination ultimately resulted in a program, namely the Non-cash Food Assistance Program (BPNT) as one of the government's innovations. However, there were obstacles experienced while the program was running, for example the breach of contract committed by E-warong in Banjarnegara Regency by denying the contents of the agreement that had been agreed between Bulog partners and E-Warong. The aim of this research is to examine how to resolve disputes effectively using normative research methods by analyzing applicable regulations. The finding of resolving this dispute was using the assistance of a third party, namely the Banjarnegara Police, with a non-litigation process through Restorative Justice because it had entered the realm of criminal acts of corruption. So, to get their civil rights back, the Banjarnegara Police are looking for a solution to resolve the dispute between Bulog Partners and E-Warong in Banjarnegara using a Restorative Justice approach.